"It's not just injecting drugs": Supervised consumption sites and the social determinants of health. (1st August 2020) - Kerman, Nick; Manoni-Millar, Stéphanie; Cormier, Luc; Cahill, Tali; Sylvestre, John
Highlights: People who inject drugs experience a range of SDOH inequities. SCSs can be a downstream intervention to addressing some SDOH inequities. Relationships with SCS staff can help to rebuild connections to healthcare services. SCSs can augment community efforts to reducing homelessness. Abstract: Background: People who inject drugs are highly vulnerable to social determinants of health (SDOH) inequities, such as homelessness, food insecurity, lack of social support, and poor access to healthcare. Supervised consumption sites (SCSs) have been developed to reduce harms associated with injection drug use but their social impacts remain largely unknown. This study explored service users' experiences with SCSs and how their service use affected their SDOH. Methods: A qualitative descriptive study design was used. Participants were recruited from an SCS in Ottawa, Canada. Data were collected using in-depth interviews ( n = 21). Data analysis involved two cycles of coding that were visibly presented in an analytic matrix. Member checking of the findings was then completed using two focus groups ( n = 7). Results: Five themes were identified with regard to how SCSs impacted the SDOH: (1) social connectedness and community, (2) emotional support and stress reduction, (3) safety and security, (4) current shelter statuses and search for housing, and (5) health service access and use. The perceived effects of SCSs in these domains were mostly positive, though the importance of being vigilant and cautious when using the services was also expressed by participants. Conclusions: SCSs represent a potential downstream intervention to addressing some of the SDOH inequities experienced by people who inject drugs. In particular, the findings indicate that SCSs can be a bridge to rebuilding service users' connections with the healthcare system and an important service in efforts to prevent unsheltered homelessness.